WADUK PENJALIN DAN KEHIDUPAN PERTANIAN MASYARAKAT PAGUYANGAN KABUPATEN BREBES TAHUN 1970-2010 - Efie Sunarya (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2016)
This study entitled Reservoir Penjalin Society of Agricultural and Life Paguyangan Brebes Year 2004-2010. The purpose of this study was to clarify the effect of farm life Penjalin Reservoir and its influence on social and economic life Paguyangan community. This study uses historical method includes four stages, namely (1) heuristic (collecting sources) in the form of books District in Figures and interviews with informants and related offices, such as reservoir management Penjalin, BPP Chief Paguyangan Agricultural District, and others; (2) criticism of sources, in order to get a source that can be justified and relevant to the issues under review; (3) interpretation (interpretation) of data obtained based on facts obtained from the informants, and (4) historiography (the writing of history) as the process of preparation of the historical facts from various sources that have been selected in a form of historical writing. District of Paguyangan located south of the capital city of Bradford with a distance of about 84 km and an altitude of approximately 342 m above sea level, while the reservoir Penjalin is ± 2.4 km south of the capital district and 12 kilometers from Paguyangan District Bumiayu. The results of this study is the first Penjalin Dam began in March 1930 and completed in May 1934, the development of agriculture in Sub Paguyangan supported by good geographical conditions, the third dam construction Penjalin influence on social life that had been developed such as in terms of education, religion and tradition, and economic life of the marked changes in livelihoods, changing facilities, changes in housing conditions and income. Keywords: Reservoir Penjalin, History of Agriculture, District Paguyangan